Towards Representative Metallurgical Sampling and Gold Recovery Testwork Programmes - Dominy, S.; O'Connor, Louisa; Glass, H.; Purevgerel, S.; Xie, Y. (2018)
Representative sampling programmes that support robust metallurgical testwork during project studies underpin process plant design. When developing a process flowsheet, the risks in achieving positive financial outcomes are minimised by ensuring optimal metallurgical sampling and testwork. The quality and type of samples used for testwork are as important as the testwork itself. The key characteristic required of any sample is that it represents some defined portion of a mineral deposit. There is a preponderance of those who think that simply stating that a metallurgical sample is “representative” is enough to make it representative. The Theory of Sampling provides an insight into the causes and magnitude of errors that may occur during the sampling of particulate materials (e.g. broken rock) and is wholly applicable to metallurgical sampling programmes. In addition, some seem to think that QA/QC and Theory of Sampling application are independent of each other. Metallurgical sampling protocols and testwork must be designed to suit the style of mineralisation in question. In support, the a priori need for evaluation programmes is the characterisation of the mineralisation type(s) and domain definition. Metallurgical sampling and testwork programmes should be fully integrated into geometallurgical studies.